Pengaruh Permainan Teka-teki Bergambar Terhadap Hasil Belajar Siswa Kelas II SDN 104200 Desa Karang Gading Labuhan Deli - Rambe, Fitri Handayani; Malinda, Leni; Lubis, Rizka Hidayah Husin (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
This study employed an experimental design involving two groups: an experimental group taught using picture puzzle games and a control group taught using conventional methods. The research aimed to examine the effect of picture puzzle games on the learning outcomes of second-grade students at SDN 104200 Karang Gading Village, Labuhan Deli. Data were analyzed using the Kolmogorov-Smirnov normality test, which revealed that the pretest and posttest scores for both the experimental and control groups were normally distributed. For the experimental group, the pretest value was 0.159, and the posttest value was 0.60 (both > 0.05), indicating normal distribution. Similarly, the control group's pretest value was 0.13, and the posttest value was 0.62 (both > 0.05). Hypothesis testing using Exact Sig. (2-tailed) showed a value of 0.000 (< 0.05), rejecting H0 and accepting H1, thus confirming the significant impact of picture puzzle games on learning outcomes. The feasibility test scored 80%, indicating good suitability for use as a learning medium. These results suggest that using picture puzzle games as a learning tool can enhance student engagement and improve learning outcomes.